Reduced semiconductor energy conversion systems - Zhang, Lei (2013)
Power converters are extensively used in energy conversion systems for converting electrical energy from one form to another. With the development of advanced semiconductor devices, modern power converters are also usually constructed with fully controllable switches, making them suitable for driving a wide range of loads. Some example applications of power converters are Uninterruptible Power Supplies (UPSs) for supporting critical loads during voltage outages, Universal Power Quality Conditioners (UPQCs) for power quality enhancement, renewable energy interfacing converters for green energy delivery and Dynamic Voltage Restorers (DVRs) for regulating load voltages. Presently, most applications use a few types of proven traditional converter topologies. These converters have long historical records, and are therefore more trusted by the industry. However, relying on the traditional converters only does not guarantee better efficiency, lower cost and innovativeness. That prompts many researchers to propose new converter topologies usually with lower component counts. Lesser components are however almost always accompanied by some performance tradeoffs. A few commonly quoted tradeoffs are loss of independency between multiple driven loads, limited amplitude and phase-shift, and much higher stresses experienced by the remaining components. These tradeoffs can be expensive at times even though components are saved. It is therefore important to note that not all reduced component topologies are rewarding. Even for those proven useful, they cannot be generalized as suitable for all applications. A detailed application study needs to be conducted before a sound judgment can be made for the considered topology especially with reduced components. The same principle applies to the nine-switch converter recently proposed for replacing the more generalized twelve-switch back-to-back converter found in many ac-ac energy conversion systems. As their names implied, the saving expected is three semiconductor switches or 25% in percentage term. This surely is an attractive saving if no severe limitation in performance is accompanied. Unfortunately, the nine-switch converter is presently burdened by high dc-link voltage and heavily limited phase-shift between its terminal outputs even though it has been proven to work in motor drives and UPSs. These limitations are however not always severe. They are application-related even though it has presently not been clarified in the literature. It is therefore the intention now to study the nine-switch converter in greater details, believing that it can bring sizable advantages if controlled, designed and applied properly. The investigation planned for the thesis is thus to revisit the nine-switch modulation principles and its existing ac-ac converter applications with an intermediate dc-link. The intention is to identify areas where modulation can be improved and quantify limitations faced by the nine-switch topology. Understanding those enables new modulation schemes to be proposed for the nine-switch converter before trying them with two suitable energy conversion systems.